2007
DOI: 10.1001/archpsyc.64.2.193
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Prefrontal Glutamate/Glutamine and γ-Aminobutyric Acid Levels in Major Depression Determined Using Proton Magnetic Resonance Spectroscopy

Abstract: Context: Increasing evidence indicates that major depressive disorder (MDD) is associated with altered function of the major excitatory and inhibitory neurotransmitters glutamate and ␥-aminobutyric acid (GABA), respectively. A recently developed magnetic resonance spectroscopy method allows for reliable measurement of glutamate/glutamine (Glx) and GABA concentrations in prefrontal brain regions that have been implicated in the pathophysiologic mechanisms of MDD by studies using other neuroimaging and postmorte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

30
513
8
20

Year Published

2009
2009
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 777 publications
(571 citation statements)
references
References 65 publications
30
513
8
20
Order By: Relevance
“…Although Hasler et al (2009) found no differences in MPFC GABA in unmedicated subjects with panic disorder or in unmedicated patients with major depressive disorder (MDD, Hasler et al, 2007), Kegeles et al (2012) found increased GABA levels in the MPFC of unmedicated patients with schizophrenia using identical methodology to ours. In more dorsal voxels, decreases in GABA levels were found in unmedicated patients with MDD (Hasler et al, 2007) and in recovered, medication-free patients with a history of MDD (Bhagwagar et al, 2008). Of note, when the four patients in our OCD sample with a history of MDD were removed, decreases in MPFC GABA levels were even more robust in OCD patients compared with controls (F 1,39 ¼ 8.079, p ¼ 0.007).…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…Although Hasler et al (2009) found no differences in MPFC GABA in unmedicated subjects with panic disorder or in unmedicated patients with major depressive disorder (MDD, Hasler et al, 2007), Kegeles et al (2012) found increased GABA levels in the MPFC of unmedicated patients with schizophrenia using identical methodology to ours. In more dorsal voxels, decreases in GABA levels were found in unmedicated patients with MDD (Hasler et al, 2007) and in recovered, medication-free patients with a history of MDD (Bhagwagar et al, 2008). Of note, when the four patients in our OCD sample with a history of MDD were removed, decreases in MPFC GABA levels were even more robust in OCD patients compared with controls (F 1,39 ¼ 8.079, p ¼ 0.007).…”
Section: Discussionmentioning
confidence: 79%
“…One is that there are Glx reductions both in pediatric and adult OCD samples, but our larger voxel diluted a more localized Glx signal difference. However, use of this larger voxel did not prevent detection of significant MPFC Glx findings in other diagnostic groups using similar methods (Hasler et al, 2007;Kegeles et al, 2012). Another possibility is that there are reduced Glx levels in pediatric but not adult OCD patients in this brain region, suggesting that the pathophysiology of pediatric and adult OCD might differ.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…A trend of lower concentration was seen in the GM voxel, but significance was lost after correcting for multiple comparisons. Since decreased glutamine/glutamate ratios were similarly observed in patients with depression and mood disorders [35,36], this may suggest the need for increased vigilance for affective disturbances in patients following LGI1 encephalitis. Considering structural MRI data indicating global atrophy, we expected a significant tNAA difference between the LGI1 patients and control subjects.…”
Section: Accepted Manuscript 12mentioning
confidence: 94%
“…In fact, FC within the DMN is increased by stress (Soares et al, 2013) and in depression (Grimm et al, 2009;Whitfield-Gabrieli and Ford, 2012). In addition to these analyses of the changes in brain function underlying depression, region-specific metabolic changes as derived from MRS have been reported for depressed patients (Hasler et al, 2007). These metabolic changes could be related to altered neuronal and glial function (Harrison, 2002;Rajkowska and Stockmeier, 2013;Yuksel and Ongur, 2010).…”
Section: Introductionmentioning
confidence: 99%